2016
DOI: 10.21082/ijas.v7n1.2006.p15-19
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Postharvest Machineries and Packaging in Minimizing Aflatoxin Contamination in Peanut

Abstract: As a tropical country with relatively high humidity and temperature, Indonesia is struggling with aflatoxin which frequently contaminates peanut. Aflatoxin is a carcinogenic toxic substance that could cause liver cancer. Due to the increasing concern on food safety, the Indonesian Drugs and Foods Agency specifies the maximum aflatoxin allowed in peanut as much as 20 ppb. However, researches showed that aflatoxin contamination in peanut in Indonesia is much higher than the threshold. The study was carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Hepsag et al detected total levels of aflatoxins in pistachio samples, ranging from 0.26 µg/kg to 385 µg/kg and from 0.16 to 60.9 µg/kg in groundnuts [48]. Fu et al, 2018 found in their study that PET is more suitable to store peanuts, pistachios, and other oleaginous products due to its good properties for maintaining the safety of the products [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…Hepsag et al detected total levels of aflatoxins in pistachio samples, ranging from 0.26 µg/kg to 385 µg/kg and from 0.16 to 60.9 µg/kg in groundnuts [48]. Fu et al, 2018 found in their study that PET is more suitable to store peanuts, pistachios, and other oleaginous products due to its good properties for maintaining the safety of the products [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…These triple-layer bags are now being marketed in Africa (Ben et al, 2009). Hermetic packaging could protect groundnuts from moulds and aflatoxin contamination (Paramawati et al, 2006). Preliminary studies have indicated the efficacy of hermetic storage of groundnut pods using triple-layer polyethylene bags in minimising aflatoxins (H. Sudini, unpublished data).…”
Section: Storage Methodsmentioning
confidence: 99%
“…Post-harvest machines, such as threshers, dryers and shellers, help to increase yield and reduce post-harvest processing and drying time. As a result, they are often associated with decreased aflatoxin contamination in groundnuts (Paramawati et al, 2006).…”
Section: Use Of Post-harvest Machinerymentioning
confidence: 99%
“…This could be attributed to the hermetic bags helping to reduce oxygen levels. Since oxygen is essential for aflatoxin production in aflatoxigenic fungi, its absence in the packages (hermetic packaging) will minimize fungal growth (Paramawati et al 2006) and hence aflatoxin production. Ellis et al (1993) also reported that aflatoxin production by A. flavus was reduced to safe and acceptable levels (\ 20 ppb) by reducing oxygen levels in packaging systems.…”
Section: Aflatoxin Productionmentioning
confidence: 99%